Como a construção de um bem público pode dar errado? O planejamento e a participação social nas entregas governamentais - Santos, Marcio Alípio dos (2015)
This Case Study for Teaching and Learning addresses the election of a politician who in his election campaign, aware of the availability of resources for use in projects related to sports, promises to reform and build squares with sports equipment. When the project was submitted for approval, it turned out that there was already a construction made on site by the residents. With the decision of the Municipality to demolish the work, there was reaction from residents who had other demands. The objective this paper is to encourage the reader to reflect on the inefficiency of planning in public administration when it disregards the needs of citizens; identify critical points of the planning process and execution of public works; and discuss concepts such as public value, participation and social control over public policies in a municipality. The various examples of unfinished works or works that surpass the initial budgets and do not benefit the population in any way show the need to reflect about the Brazilian government planning.